Isolation, culture, and characterisation of bovine ovarian fetal fibroblasts and gonadal ridge epithelial-like cells and comparison to their adult counterparts. - Menghe Liu; Katja Hummitzsch; Nicole A Bastian; Monica D Hartanti; Qianhui Wan; Helen F Irving-Rodgers; Richard A Anderson; Raymond J Rodgers (PLoS ONE)
During ovarian development, gonadal ridge epithelial-like (GREL) cells arise from the epithelial cells of the ventral surface of the mesonephros. They ultimately develop into follicular granulosa cells or into ovarian surface epithelial cells. Stromal fibroblasts arise from the mesonephros and penetrate the ovary. We developed methods for isolating and culturing fetal ovarian GREL cells and ovarian fibroblasts by expansion of colonies without passage. In culture, these two cell types were morphologically different. We examined the expression profile of 34 genes by qRT-PCR, of which 24 genes had previously been studied in whole fetal ovaries. Expression of nine of the 10 newly-examined genes in fetal ovaries correlated with gestational age (MUC1, PKP2, CCNE1 and CCNE2 negatively; STAR, COL4A1, GJA1, LAMB2 and HSD17B1 positively). Comparison between GREL cells and fetal fibroblasts revealed higher expression of KRT19, PKP2, OCLN, MUC1, ESR1 and LGR5 and lower expression of GJA1, FOXL2, NR2F2, FBN1, COL1A1, NR5A1, CCND2, CCNE1 and ALDH1A1. Expression of CCND2, CCNE1, CCNE2, ESR2 and TGFBR1 was higher in the fetal fibroblasts than in adult fibroblasts; FBN1 was lower. Expression of OCLN, MUC1, LAMB2, NR5A1, ESR1, ESR2, and TGFBR3 was lower in GREL cells than ovarian surface epithelial cells. Expression of KRT19, DSG2, PKP2, OCLN, MUC1, FBN1, COL1A1, COL3A1, STAR and TGFBR2 was higher and GJA1, CTNNB1, LAMB2, NR5A1, CYP11A1, HSD3B1, CYP19A1, HSD17B1, FOXL2, ESR1, ESR2, TGFBR3 and CCND2 was lower in GREL cells compared to granulosa cells. TGFβ1 altered the expression of COL1A1, COL3A1 and FBN1 in fetal fibroblasts and epidermal growth factor altered the expression of FBN1 and COL1A1. In summary, the two major somatic cell types of the developing ovary have distinct gene expression profiles. They, especially GREL cells, also differ from the cells they ultimately differentiate in to. The regulation of cell fate determination, particularly of the bi-potential GREL cells, remains to be elucidated.